Підходи до оцінки ефективності АСУ інформаційними технологіями - Шеховцова, В. І. (НТУ "ХПІ", 2014)
Пропонуються підходи щодо оцінки якості автоматизованої системи управління та функціональної ефективності ІТ-архітектури підприємства. Наводиться алгоритм процесу оцінки ефективності управління як поетапна послідовність дій по визначенню певних показників за обумовленими критеріями. Виділяються шляхи досягнення сумісності забезпечень АСУ по видам і рівням управління. Показана модель процесу моніторингу та оцінки ІТ технологій на підприємстві, що узагальнює підходи за різними критеріями.

Approaches to evaluating the quality of the automated control system and the functional efficiency of IT-enterprise architecture. An algorithm for evaluating the effectiveness of management processes as stepwise sequence of actions aimed at identifying specific indicators for specific criteria. Allocated towards achieving interoperability of ACS support for types and levels of management. Shows a model of the process of monitoring and evaluation of IT technologies in the enterprise, which summarizes the approaches according to various criteria. The article provides a list of major international and national standards, regulatory issues of design, implementation and evaluation of the quality management of information technology in the management of enterprises. The variants of calculations evaluating the effectiveness of information technology in the enterprise, which are based on an analysis of the validity and utility and necessity of creation and implementation of an automated control system. The ways of increasing the economic efficiency of application of information technologies in the management of the organization.
Approaches to evaluation of effectiveness acs from information technologies
Keywords: автоматизовані системи управління; моніторинг; сумісність; information technology; automatic control system; assessment of efficiency; monitoring; compatibility